Numerical Investigation on Suppressing High Frequency Self-Excited Noises of Armature Assembly in a Torque Motor Using Ferrofluid - Hasiaoqier Han; Songjing Li; Liang Guo; Qingwen Wu (Shock and Vibration)
Attempting to suppress high frequency self-excited noises of armature assembly, ferrofluid is added to the working clearances of torque motor. The mathematical model of resistance force of ferrofluid applied to armature is derived theoretically from parallel plate squeeze flow theory and ferrofluid constitutive model in which shear thickening and shear thinning effects are taken into account. Then the equivalent physical model of ferrofluid is established according to the resistance force, and, through analysis, it can be further simplified as viscous damping model. Finally, the suppressing effect introduced by ferrofluid on high frequency noises of armature assembly is verified by comparing the results of numerical simulation with ferrofluid and that without ferrofluid.